Impact of short-term extreme temperature events on physiological performance of Salicornia ramosissima J. Woods under optimal and sub-optimal saline conditions - Pérez-Romero, Jesús Alberto (Sci Rep, 2019)
Increasing extreme temperature climatic events could exert an important effect on plant photosynthetic performance, which could be modulated by the co-occurrence with other environmental factors, such as salinity, in estuarine ecosystems. Therefore, a mesocosm experiment was designed to assess the impact of temperature events for three days (13/5 °C, 25/13 °C and 40/28 °C) in combination with two NaCl concentrations (171 and 1050 mM NaCl) on the physiological performance of Salicornia ramosissima. Extreme temperature events had a negative impact on S. ramosissima photosynthetic efficiency, this effect being more marked with cold wave at both salinities, compared with heat wave, even in presence of NaCl excess. This differential thermotolerance in the photosynthetic apparatus was ascribed to the greater integrity and functioning of its photosynthetic pathway at high temperature, as indicated by constant g(s,) V(c,max) values at optimal salinity and the higher values of those parameters and g(m) recorded in combination with NaCl excess. Moreover, S. ramosissima was able to upregulate the energy sink capacity of its photochemical apparatus at elevated temperature and salinity by a greater energy excess dissipation capacity. This could have contributed to reducing the risk of oxidative stress, along with the recorded higher capacity for antioxidant enzyme activity modulation under these conditions.